2020
DOI: 10.17221/105/2019-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

African swine fever virus (ASFV) in Poland: Prevalence in a wild boar population (2017-2018)

Abstract: African swine fever (ASF) was first described in 1921 in Kenya. The latest epidemic of ASF started in 2007 in Georgia. The virus was introduced to Poland in 2014. Since the beginning of the epidemics, the National Veterinary Research Institute in Pulawy (NVRI) has been testing wild boar samples from restricted areas and other parts of Poland to conduct passive and active surveillance for ASFV in these groups of animals. The aim of this study was to summarise the last two years of the ASF epidemiological status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 23 publications
4
42
0
1
Order By: Relevance
“…Dead wild boar may therefore disappear faster from the environment in this season, which might explain the low numbers of dead wild boar detected in June. In Poland, similar patterns were found and the numbers of samples from passive surveillance were high in July, while it seems that they were significantly lower in June [ 38 ].…”
Section: Discussionmentioning
confidence: 54%
“…Dead wild boar may therefore disappear faster from the environment in this season, which might explain the low numbers of dead wild boar detected in June. In Poland, similar patterns were found and the numbers of samples from passive surveillance were high in July, while it seems that they were significantly lower in June [ 38 ].…”
Section: Discussionmentioning
confidence: 54%
“…This specific region, called Warsaw cluster, presented as one of the most affected areas by then, therefore in 2018 and 2019 over 2600 ASF cases were confirmed there. Moreover, from the beginning of the disease epidemiology, two distinct clusters might be observed there: southeastern and northwestern to Warsaw, separated by the center of the city and expressway S8 ( Figure 2 ) [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…ASFV epidemics nearby Warsaw city began at the end of 2017, and in 2019 over 1500 infected wild boars were confirmed within this cluster. Moreover, from the beginning of the disease epidemiology, two distinct clusters might be observed there, namely the southeastern and northwestern clusters to Warsaw, separated by the center of the city and S8 expressway [ 15 ]. The previous study showed that all tested samples, which were located in the southeastern cluster, possess a unique tandem repeat within the O174L gene [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, methods that account for re-introduction and surveillance design are important in cases where 'single introduction' and 'perfect detection' assumptions are violated. Similar to many wildlife host-pathogen systems [31,[33][34][35], ASFv surveillance in wild boar is mostly passive [36] with only a small proportion of cases likely being detected (e.g., for ASFv in Poland: ≤ 30% of all ASFv carcasses detected by carcass surveillance, ≤ 1.7% of all active ASFv infections detected by hunter harvest, [26]), and genetic evidence suggests that at least two re-introductions from neighboring regions occurred during the time frame of our study [37].…”
Section: Introductionmentioning
confidence: 99%